2020
DOI: 10.1186/s12944-020-01348-x
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of long non-coding RNA expression profiles in low high-density lipoprotein cholesterol disease

Abstract: Background: Low high-density lipoprotein cholesterol (HDL-C) disease with unknown etiology has a high prevalence in the Xinjiang Kazak population. In this study, long noncoding RNAs (lncRNAs) that might play a role in low HDL-C disease were identified. Methods: Plasma samples from 10 eligible individuals with low HDL disease and 10 individuals with normal HDL-C levels were collected. The lncRNA profiles for 20 Xinjiang Kazak individuals were measured using microarray analysis. Results: Differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Xiao-Hua Yu et al found that lncRNA kcnq1ot1 overexpression markedly decreased plasma HDL-C level, and kcnq1ot1 could promote lipid accumulation and accelerate the development of atherosclerosis through the miR-452-3p/HDAC3/ABCA1 pathway ( 22 ). Moreover, Xinping Wang et al performed microarray analysis of long non-coding RNA expression profiles in low high-density lipoprotein cholesterol disease and found that certain lncRNAs could cause low high-density lipoprotein cholesterol disease ( 23 ). LncRNAs could modulate the transfer of lipid molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao-Hua Yu et al found that lncRNA kcnq1ot1 overexpression markedly decreased plasma HDL-C level, and kcnq1ot1 could promote lipid accumulation and accelerate the development of atherosclerosis through the miR-452-3p/HDAC3/ABCA1 pathway ( 22 ). Moreover, Xinping Wang et al performed microarray analysis of long non-coding RNA expression profiles in low high-density lipoprotein cholesterol disease and found that certain lncRNAs could cause low high-density lipoprotein cholesterol disease ( 23 ). LncRNAs could modulate the transfer of lipid molecules.…”
Section: Introductionmentioning
confidence: 99%